PENINGKATAN KUALITAS PEMBELAJARAN PPKN MELALUI MODEL MAKE A MATCH BERBANTUAN POWER POINT PADA SISWA KELAS IIIB SDN SIDOKARE 2 SIDOARJO: IMPROVING THE QUALITY OF PPKN LEARNING THROUGH THE MAKE A MATCH MODEL ASSISTED WITH POWER POINTS IN CLASS IIIB STUDENTS OF SDN SIDOKARE 2 SIDOARJO - Auliya, Nasrul (J-SES : Journal of Science, Education and Studies, 2024)
The purpose of PPKn is to foster national insight and awareness, attitudes and behavior that love the motherland and are based on national culture, insight into the archipelago, and national resilience in prospective successors to the nation who are studying and will master science, technology and art. Based on the initial reflections that were made that the teacher had not been able to utilize the media, the students also did not focus on the teacher's explanation during the learning process. The solution to overcome this problem is by applying the Make A Match Type Cooperative Model Assisted by PowerPoint. This learning model is one type of method in cooperative learning. Make A Match or looking for a partner is a cooperative learning technique that can develop students' abilities and the advantage of this technique is that it is able to create an active, conducive and fun learning atmosphere for students in participating in learning. The formulation of the problem is whether using the PowerPoint-Assisted Make A Match Type Cooperative model can improve the quality of Civics lessons? While the purpose of this research is to increase student activity, and student learning outcomes. The variables of this study are learning outcomes, student activities, student motivation, and student interaction in Civics learning. This research is a classroom action research consisting of 3 cycles with the stages of planning, action, observation and reflection. The research subjects were class IIIB students of SDN Sidokare 2 Sidoarjo. This data collection technique is in the form of observation, interviews, and test methods. Data about student activity and motivation as well as suitability of scenarios in the learning process use observation techniques. Description test method to obtain data on the percentage of students who can answer correctly and incorrectly. Data analysis used descriptive qualitative analysis. The results of research in the first cycle of student learning outcomes in the first cycle of student completeness by 60%, in the second cycle of student completeness increased to 84.5%, and to 90% in the third cycle of student learning outcomes get an average score in the good category. Student activity in cycle I got 70.1%, in cycle II it increased to 80.5%, and to 90% in cycle III the results of student activity were in the good category according to the expected maximum percentage. Student motivation in cycle I was 65.3%, in cycle II it increased to 70% but for student learning motivation it still did not reach the expected maximum percentage, in cycle III it was 85% the results of student motivation were in a good category according to the maximum percentage expected . Student interaction in cycle I was 75%, in cycle II it increased to 80.3%, and to 87.5% in cycle III the results of student interaction at the beginning of the cycle had reached the expected maximum percentage. Node through the application of the PowerPoint-Assisted Make A Match Type Cooperative model can improve student learning outcomes, student activities, student motivation and class IIIB student interaction at SDN Sidokare 2 Sidoarjo in Civics learning. Suggestions for teachers to apply the Make A Match model not only in Civics subjects, but also in other subjects to make it more effective and efficient.